2020
DOI: 10.1111/cas.14557
|View full text |Cite
|
Sign up to set email alerts
|

FOXO1 inactivation induces cisplatin resistance in bladder cancer

Abstract: We found that FOXO1‐shRNA sublines or FOXO1‐positive cells co–treated with a FOXO1 inhibitor were significantly more resistant to cisplatin treatment at pharmacological concentrations, compared with respective control sublines or those with mock treatment. Western blot demonstrated considerable increases in the expression levels of a phosphorylated inactive form of FOXO1 (p‐FOXO1) in cisplatin‐resistant sublines established by long‐term culture with low/increasing doses of cisplatin, compared with respective c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 11 publications
0
13
0
Order By: Relevance
“…In these cisplatin-resistant cells, E2 treatment was also found to increase the expression and activity of b-catenin known to contribute to cisplatin resistance. We additionally showed that FOXO1, which could be inactivated via the ERb pathway as described above (69), was also inactivated in cisplatin-resistant bladder cancer cells and that FOXO1 knockdown or inhibitor treatment significantly induced resistance to cisplatin in bladder cancer cells (83). Meanwhile, in transurethral resection specimens from those, especially female patients, who subsequently received cisplatin-based neoadjuvant chemotherapy prior to radical cystectomy, loss of ERb immunoreactivity was strongly associated with favorable chemoresponse (35).…”
Section: Role Of Er In Sensitivity To Conventional Non-surgical Therapymentioning
confidence: 92%
See 1 more Smart Citation
“…In these cisplatin-resistant cells, E2 treatment was also found to increase the expression and activity of b-catenin known to contribute to cisplatin resistance. We additionally showed that FOXO1, which could be inactivated via the ERb pathway as described above (69), was also inactivated in cisplatin-resistant bladder cancer cells and that FOXO1 knockdown or inhibitor treatment significantly induced resistance to cisplatin in bladder cancer cells (83). Meanwhile, in transurethral resection specimens from those, especially female patients, who subsequently received cisplatin-based neoadjuvant chemotherapy prior to radical cystectomy, loss of ERb immunoreactivity was strongly associated with favorable chemoresponse (35).…”
Section: Role Of Er In Sensitivity To Conventional Non-surgical Therapymentioning
confidence: 92%
“…Further clinical studies are thus required for determining the actual benefit of anti-estrogen (or estrogen) treatment in patients with urothelial cancer. In particular, more convincing preclinical data exist to predict enhanced sensitivity to conventional non-surgical therapy against bladder cancer via anti-estrogens ( 35 , 50 , 70 , 80 , 81 , 83 ). In these studies, the role of ERα/ERβ expression in clinical samples, as a predictor of therapeutic response, may also need to be explored.…”
Section: Clinical Trials Of Er Modulation In Bladder Cancermentioning
confidence: 99%
“…Although resistance to CDDP-based chemotherapy is not uncommonly seen in patients with urothelial cancer, its underlying mechanisms are not fully understood. Meanwhile, AR activation in bladder cancer cells has been implicated to be associated with chemoresistance [ 12 , 13 , 14 , 15 , 21 , 22 , 23 , 24 ]. In the present study, we further investigated the role of GULP1, as a downstream target of AR, in CDDP resistance, using bladder cancer cell lines as well as surgical specimens.…”
Section: Discussionmentioning
confidence: 99%
“…As aforementioned, both androgen and estrogen could inactivate a tumor suppressor FOXO1 via the AR and ERβ pathways, respectively, in bladder cancer cells [ 32 ]. We further found that silencing of FOXO1 or treatment with an FOXO1 inhibitor in bladder cancer cells resulted in the reduction of sensitivity to cisplatin [ 77 ]. The expression of an inactivated form phospho-FOXO1 was considerably up-regulated in cisplatin-resistant cells, compared with control cells, and phospho-FOXO1 expression in transurethral resection specimens from patients undergoing cisplatin-based neoadjuvant chemotherapy was more often seen in non-responders (67.9%) than in responders (38.9%) [ 77 ].…”
Section: Sex Hormone Receptor Signaling and Sensitivity To Conventional Non-surgical Treatment For Bladder Cancermentioning
confidence: 99%
“…We further found that silencing of FOXO1 or treatment with an FOXO1 inhibitor in bladder cancer cells resulted in the reduction of sensitivity to cisplatin [ 77 ]. The expression of an inactivated form phospho-FOXO1 was considerably up-regulated in cisplatin-resistant cells, compared with control cells, and phospho-FOXO1 expression in transurethral resection specimens from patients undergoing cisplatin-based neoadjuvant chemotherapy was more often seen in non-responders (67.9%) than in responders (38.9%) [ 77 ]. FOXO1 inactivation could thus be an underlying mechanism for chemoresistance in bladder cancer induced by AR and/or ERβ signals.…”
Section: Sex Hormone Receptor Signaling and Sensitivity To Conventional Non-surgical Treatment For Bladder Cancermentioning
confidence: 99%